Sustainability of Solar Electricity : The Role of Endogenous Resource Substitution and Market Mediated Responses - Steinbuks, Jevgenijs; Satija, Gaurav; Zhao, Fu (World Bank Group, Washington, DC, 2015)
This study seeks to understand how materials scarcity and competition from alternative uses affects the potential for widespread deployment of solar electricity in the long run, in light of related technology and policy uncertainties. Simulation results of a computable partial equilibrium model predict a considerable expansion of solar electricity generation worldwide in the near decades, as generation technologies improve and production costs fall. Increasing materials scarcity becomes a significant constraint for further expansion of solar generation, which grows considerably slower in the second half of the coming century. Solar generation capacity increases with higher energy demand, squeezing consumption in industries that compete for scarce minerals. Stringent climate policies hamper growth in intermittent solar photovoltaics backed by fossil fuel powered plants, but lead to a small increase in non-intermittent concentrated solar power technology. By the end of the coming century, solar electricity remains a marginal source of global electricity supply even in the world of higher energy demand, strict carbon regulations, and generation efficiency improvements.